2010
DOI: 10.1080/02640414.2010.504783
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of GPS for measuring distance travelled in field-based team sports

Abstract: The aim of the present study was to examine the effects of movement intensity and path linearity on global positioning system (GPS) distance validity and reliability. One participant wore eight 1-Hz GPS receivers while walking, jogging, running, and sprinting over linear and non-linear 200-m courses. Five trials were performed at each intensity of movement on each 200-m course. One receiver was excluded from analysis due to errors during data collection. The results from seven GPS receivers showed the mean (± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(112 citation statements)
references
References 17 publications
9
94
2
3
Order By: Relevance
“…This is an 2 interesting finding as high intensity running distance has been reported to distinguish the 3 standard of senior soccer players (25). This may be because the players from the current 4 study spent a lower proportion of match time in high intensity running compared to the senior 5 professional soccer players (4) possibly due to a difference in the area per player (27) 6 between the current and previous (4) studies or because the anaerobic energy supplying 7 pathways will not be fully developed in boys of this age (13,16,22). 8 9 In summary, the total distance covered during a match was approximately 4000 m for the U9 10 and U10 elite soccer players and only 600-700 m were covered by high intensity running 11 which was achieved during 5-6% of match playing time.…”
Section: Match Analysis Of Youth Soccer 22mentioning
confidence: 54%
“…This is an 2 interesting finding as high intensity running distance has been reported to distinguish the 3 standard of senior soccer players (25). This may be because the players from the current 4 study spent a lower proportion of match time in high intensity running compared to the senior 5 professional soccer players (4) possibly due to a difference in the area per player (27) 6 between the current and previous (4) studies or because the anaerobic energy supplying 7 pathways will not be fully developed in boys of this age (13,16,22). 8 9 In summary, the total distance covered during a match was approximately 4000 m for the U9 10 and U10 elite soccer players and only 600-700 m were covered by high intensity running 11 which was achieved during 5-6% of match playing time.…”
Section: Match Analysis Of Youth Soccer 22mentioning
confidence: 54%
“…12,14,15 While these studies provided a thorough assessment of velocity, acceleration, and deceleration compared with high-sampling criterion measures, the limitations were that they did not assess using sport-specific movements involving changes in direction. Other studies have employed sport-specific movement circuits, 8,11,[16][17][18][19] however most of these studies are limited in the criterion measures used to evaluate velocity (eg, timing gates, 20,21 ) and synchronization protocols are not well documented.…”
Section: Reliability and Validity Of Commercial Gps Devicesmentioning
confidence: 99%
“…For the distance traveled between 14.4 and 21.5 km/h, higher %SEM values were found (30.0 to 42.0%), but also close to those found by Ade et al 4 (40-60%) in a similar speed range (14.5-19.8 km/h). In fact, studies have shown a decrease in reliability for higher speeds in SSG using 1Hz, 5Hz, and 10Hz GPS 7,8,19 . This may be related to the low sampling frequency of GPS devices, which limits the capture of short movements at high speeds 20 .…”
Section: Discussionmentioning
confidence: 99%